2006
DOI: 10.1111/j.1423-0410.2006.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Dombrock gene analysis in Brazilian people reveals novel alleles

Abstract: Our data demonstrate high heterogeneity of DO alleles in the Brazilian population. Our study also highlights the importance of testing a cohort of different populations to determine DO haplotypes and of establishing reliable genotyping tests for predicting Doa/Dob status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…The haplotype frequencies for the four ethnic cohorts are shown (Table 5). This analysis confirmed earlier results 3,7,26 that SNPs at nucleotides 378 and 624 are not invariably associated with the Do type. The critical SNP is at nucleotide 793.…”
Section: Expanded Hea With Gypb Silencing Mutationssupporting
confidence: 93%
“…The haplotype frequencies for the four ethnic cohorts are shown (Table 5). This analysis confirmed earlier results 3,7,26 that SNPs at nucleotides 378 and 624 are not invariably associated with the Do type. The critical SNP is at nucleotide 793.…”
Section: Expanded Hea With Gypb Silencing Mutationssupporting
confidence: 93%
“…Genotyping studies in this population have shown that the blood group polymorphisms differ significantly from other populations6, 7 and studies inside the country have also shown a heterogeneous distribution of blood group alleles and variants between groups of people from different regions 8, 9. Moreover, the high degree of genetic mixture in the Brazilian population facilitates the generation of new alleles 10, 11. Therefore, studies on the distribution of blood group alleles and variants in donors and patients from different regions of Brazil can report the frequencies of defined polymorphic blood group antigens that function as receptors for parasites, map the rare phenotypes across the country and contribute in the selection of the most adequate blood component for chronically transfused patients.…”
mentioning
confidence: 81%
“…Subjects provided informed consent and the study was approved by the institutional review board. The sample size was calculated assuming a significance level of 5% and 80% power in relation to the prevalence of the DO*B-WL allele which has previously been identified in a Brazilian population (11) .…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, three new alleles have already been identified: DO*B-WL (898C>G), DO*A-SH (624T>C), and DO*A-WL (898C>G) (5,11) . In addition, molecular studies of the DO alleles revealed that JO is more common than HY in Brazil, whereas HY is more prevalent in New York (12) .…”
Section: Introductionmentioning
confidence: 99%